2006
DOI: 10.1002/path.1917
|View full text |Cite
|
Sign up to set email alerts
|

Higher neutrophil infiltration mediated by osteopontin is a likely contributing factor to the increased susceptibility of females to alcoholic liver disease

Abstract: Alcoholic liver disease (ALD) is a major public health problem in the United States and women are known to be more susceptible to ALD. However, the precise mechanism for increased susceptibility of females to ALD is not completely understood. The present study is based on the hypothesis that induction of osteopontin (OPN), a matricellular protein, is the likely contributing factor for higher neutrophil recruitment in females during alcoholic steatohepatitis (ASH). ASH was induced in male and female Sprague-Daw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
88
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 60 publications
7
88
0
Order By: Relevance
“…It has been shown to be a chemoattractant for macrophages and neutrophils both in vitro and in vivo (Bayless et al, 1998, Apte et al, 2005. Recent studies from our laboratory have shown that OPN acts as a chemokine in attracting neutrophils to the liver, making it more susceptible to injury in alcoholic steatohepatitis (ASH) (Apte et al, 2005;Banerjee et al, 2006). We have also reported that neutralizing antibodies directed against OPN significantly decrease neutrophil infiltration into the hepatic parenchyma in our rodent model of ASH (unpublished data).…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…It has been shown to be a chemoattractant for macrophages and neutrophils both in vitro and in vivo (Bayless et al, 1998, Apte et al, 2005. Recent studies from our laboratory have shown that OPN acts as a chemokine in attracting neutrophils to the liver, making it more susceptible to injury in alcoholic steatohepatitis (ASH) (Apte et al, 2005;Banerjee et al, 2006). We have also reported that neutralizing antibodies directed against OPN significantly decrease neutrophil infiltration into the hepatic parenchyma in our rodent model of ASH (unpublished data).…”
Section: Introductionsupporting
confidence: 57%
“…A recent study from our laboratory has clearly shown that administration of neutralizing antibody against OPN abolishes hepatic neutrophilic infiltration and prevents ethanol-induced liver injury (Banerjee et al, 2006). Measurement of OPN protein in the liver to assess neutrophil infiltration has potential limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophils (the majority of PMNs) are the primary responder to exogenous and endogenous stimuli and rapidly infiltrate the injured tissue to initiate an innate host defense. OPN is a chemoattractant for neutrophils (Weiss et al, 2001;Banerjee et al, 2006;Koh et al, 2007). Activated neutrophils release proteases and cytotoxic mediators in combination with phagocytosis and respiratory bursts to eliminate invading infectious agents.…”
Section: Neutrophilsmentioning
confidence: 99%
“…However, cytotoxic products released by neutrophils may also cause host tissue destruction such as observed in inflammatory bowel disease . OPN has been found to play an important role in neutrophil recruitment in alcoholic liver disease (Apte et al, 2005;Banerjee et al, 2006). The expression and localization of CD44 in neutrophils is independent of OPN, although CD44 is required for the polarization and chemotaxis of neutrophils (Alstergren et al, 2004).…”
Section: Neutrophilsmentioning
confidence: 99%